2018
DOI: 10.1002/cbin.10955
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa infection alters the macrophage phenotype switching process during wound healing in diabetic mice

Abstract: Macrophages play critical roles in wound healing process. They switch from "classically activated" (M1) phenotype in the early inflammatory phase to "alternatively activated" (M2) phenotype in the later healing phase. However, the dynamic process of macrophage phenotype switching in diabetic wounds burdened with bacteria is unclear. In this report, Pseudomonas aeruginosa, frequently detected in diabetic foot ulcers, was inoculated into cutaneous wounds of db/db diabetic mice to mimic bacterium-infected diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
1
22
0
2
Order By: Relevance
“…Despite forming large abscesses, their structure had diffused immune cell organization and higher bacterial burdens (148). In mice infected with P. aeruginosa, diabetes was associated with prolonged M1 activation, which impaired healing processes by diminishing re-epithelialization, granulation tissue formation and angiogenesis (158). Alternatively, Nguyen et al found diabetic mice inoculated with S. aureus biofilms had reduced TLR2 and TLR4 mRNA expression and high levels of inflammatory cytokines (IL-1b and TNF-a) (159).…”
Section: Other Modifiers Of Host Antibacterial Immune Responses In the Wound Microenvironmentmentioning
confidence: 99%
“…Despite forming large abscesses, their structure had diffused immune cell organization and higher bacterial burdens (148). In mice infected with P. aeruginosa, diabetes was associated with prolonged M1 activation, which impaired healing processes by diminishing re-epithelialization, granulation tissue formation and angiogenesis (158). Alternatively, Nguyen et al found diabetic mice inoculated with S. aureus biofilms had reduced TLR2 and TLR4 mRNA expression and high levels of inflammatory cytokines (IL-1b and TNF-a) (159).…”
Section: Other Modifiers Of Host Antibacterial Immune Responses In the Wound Microenvironmentmentioning
confidence: 99%
“…Chronic wounds are frequently accompanied by the invasion and infection of bacteria due to their unique microenvironment. Multiple species of bacteria have been isolated from chronic wounds, and several also affect the M1 to M2 polarization of macrophages (128). For example, Pseudomonas aeruginosa (P. aeruginosa) is a frequently detected gram-negative pathogen in diabetic non-biofilm wounds (129,130).…”
Section: Numerous Microenvironmental Biomolecules For Impaired M1 To M2 Polarizationmentioning
confidence: 99%
“…and growth factors [insulin-like growth factor 1 (IGF1), vascular endothelial growth factor (VEGF), transforming growth factor (TGF), etc.]. [15][16][17][18][19] M1 and M2 ATMs constitute different subsets of macrophages. Insulin resistance and adipose tissue inflammation are related to the number of M1 macrophages and the expression of M1 marker genes, such as Tnfa and Mcp1.…”
Section: Introductionmentioning
confidence: 99%